DISADVANTAGES AND ADVANTAGES OF CREDIT-MODULAR TRAINING IN THE FIELD OF PHYSICAL EDUCATION - V.I. Marchyk; I.L. Minzhorina; T.Yu. Bryutova (Academy of Cognitive and Natural Sciences, 2008)
The article the analysis of scientific literature dealing with the problems of the development of physical training according to the Bologna Process.